Do online communities support research collaboration?. Issue 6 (11th November 2014) - R. Jamali, Hamid; Russell, Bill; Nicholas, David; Watkinson, Anthony
Abstract : Purpose: – The purpose of this paper is to explore the extent to which academics are engaged with online communities for research purposes, and the research activities, platforms and tools associated with these communities. In addition, the paper aims to discover the benefits, disadvantages and barriers involved in the use of online communities, and especially in regard to the trust and authority issues, so important in scholarly communications. Design/methodology/approach: – A layered, mixed-methods approach was used for this complex research topic. Interviews were undertaken with social science and humanities researchers, followed up with focus groups in both the USA and UK. This qualitative work was then followed up with an online questionnaire that generated over 1, 000 responses. Findings: – Over half the sample had experience of an online research community and a majority of researchers are making at least occasional use of one or more Web 2.0 services for communicating their research activity; for developing and sustaining networks and collaboration; or for finding out what others are doing. Big differences exist in membership rates according to subject, but not really by age or other demographic factors. The biggest benefit to joining an online community is the ability to seek information in one's own specialism. Younger researchers are more engaged with online communities. Research limitations/implications: – The qualitative research was limited to the UK and USA. While use of online communities is now accepted by both established and younger researchers, the main ways of communicating research remain scholarly journals and books. Practical implications: – The implications for learned societies and publishers are not clear. Journals are confirmed as the primary way of disseminating research. However, it would be easy for these stakeholders to miss how younger researchers expect to connect in digital communities. Social implications: – With researchers of all ages accepting the existing and importance of online communities and connections, there are few technical or social barriers to using mainstream digital tools to connect professionally. Originality/value: – There is little published research considering the role of online research communities, so the study is highly original. It is valuable to discover that researchers still prefer to share research findings primarily through journals, rather than through social technologies.